Care management actions in the Family Health Strategy - Marcelo Costa Fernandes; Lucilane Maria Sales da Silva; Maria Rocineide Ferreira da Silva; Thereza Maria Magalhães Moreira (Rev Rene)
Objective: to identify, from nurses’ speeches, the actions that enable care management in the Family Health Strategy.Methods: descriptive study with a qualitative approach conducted with 32 nurses of primary care. It was used a semistructuredinterview as the data collection technique. The methodological process of the collective subject discourse wasused to organize the data Results: from the nurses’ speeches one identified the categories: complementary relationshipbetween care and management; meeting with community health agents, a care management strategy in nurses’ work;health education activities such as a care management action and a health information system as an essential tool forcare Conclusion: it was possible to observe that nurses understood the importance of coordination and complementaritybetween the activities of the working process of care and management.